Learning Grammatical Topics through Music as an Intercultural Link. Didactic Proposal for a Summer Course at the University of Las Palmas de Gran Canaria (BEOIBERÍSTICA - Journal of Iberian, Latin American and Comparative Studies (ISSN: 2560-4163 Online), 2018)
The aim of the study is to enhance music as a didactic resource for the correct acquisition of grammatical knowledge of Spanish considered problematic at the time of approaching the study of our language: the use of the subjunctive, the unstressed personal pronouns and the verbs ser and estar. We also try to stimulate interest in research and personal autonomy, as well as encouraging intercultural relations and reinforcing the values of tolerance and camaraderie. It is a didactic proposal for the classroom of Spanish as a foreign language (ELE) aimed at students of level B2 in accordance with the guidelines of the Common European Framework of Reference for Languages.Broadly speaking, an active methodology is proposed, where tasks act as acquisition engines of communicative competence, applying the theory of practical assumptions such as songs. Finally, regarding the research methodology, we will stop at the presentation of the theoretical foundations, as well as the methodological approaches, which we consider fundamental, since they are the foundation of our proposal.Regarding the results of our field study, we have been able to meet the aims set at the beginning, that is: the acquisition of fixed grammatical knowledge and the achievement and encouragement of intercultural relations among students, thanks to the mentioned methodology implemented in the ELE classroom.Key words: interculturality, songs, grammar, lexicon.